Glutathione S-transferase A1 (GSTA1) as a marker of acetaminophen-induced hepatocyte injury in vitro. (24th July 2017) - Li, Rui; Liu, Fangping; Chang, Yicong; Ma, Xin; Li, Minmin; Li, Changwen; Shi, Chenxi; He, Jingshan; Li, Ying; Li, Zhi; Lin, Yuexia; Han, Qing; et al.
Abstract: Acetaminophen (APAP) overdose causes serious hepatocyte injury, and new markers are needed to predict APAP-induced hepatic injury. Glutathione S-transferase A1 (GSTA1) plays a significant role in the metabolism of APAP. Primary mouse hepatocytes were isolated by a two-step perfusion in situ . An APAP-induced hepatocyte injury model was used to characterize GSTA1 in APAP treated cells and determine whether GSTA1 could be a prognostic marker in vitro . A significant increase ( p < .05) in GSTA1 in cell culture supernatant was detected at 6 h after APAP treatment, while alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione (GSH) showed marked differences ( p < .05) at 8 h after APAP exposure, 2 h later than GSTA1. Furthermore, GSTA1 increased in a dose-dependent manner with APAP treatment. GSTA1 increased significantly ( p < .05) at a concentration of 5.0 mmol/L APAP, while the marked changes in ALT, AST and other indexes were undetectable until the concentration of APAP reached 7.5 mmol/L. These results suggest that increased GSTA1 can be more sensitive than ALT and other indexes as a marker of APAP-induced hepatic injury, which provide novel diagnostic index for APAP-induced hepatic injury and supply valuable information to further understand the pathogenesis of liver damage.